Digital Transformation in the Utilization of Technology and Applications to Increase Productivity and Sustainability of Small and Medium Enterprises (SMEs) in Pematang Serai Village, Langkat Regency - Yusup, Mohammad; Lesmana, Muhammad Donni; Arpan, Arpan; Kurniawan, Rezky (Formosa Journal of Applied Sciences, 2024)
This study aims to analyze the role of digital transformation in encouraging increased productivity and sustainability of small and medium enterprises (SMEs) in Pematang Serai Village, Langkat Regency. Amidst the development of the digital economy, the adoption of digital technology and applications is considered important to help SMEs optimize operational processes, expand market reach, and increase business resilience in facing increasingly complex challenges and competition. The research method uses a qualitative descriptive approach, with data collection techniques in the form of in-depth interviews and participatory observation. Respondents consisted of SME actors who participated in digital training programs, who provided data on experiences and challenges in implementing technology. The results of the study show that digital transformation through training and mentoring in digital literacy, financial management, and digital marketing can increase operational efficiency and competitiveness of SMEs.